2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--5785
|View full text |Cite
|
Sign up to set email alerts
|

One Size Does Not Fit All: Impact Of Varied Freshman Design Experiences On Engineering Self Efficacy

Abstract: This paper presents results of a two year pilot program in freshman design. The program's goal was to create a variety of project-based learning, or PBL, freshman experiences in design and complex problem solving as a means of energizing a fundamentals-focused math and science freshman curriculum. A second goal was to develop students' self-efficacy in a range of abilities associated with engineering including design, problem solving, innovation, communication, teamwork, application of fundamental engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Chachra et al [38] found that tinkering and technical selfefficacy did not appear to change over the duration of a team-based engineering course, which they attributed to students taking on tasks that played to pre-existing strengths, which in some cases, reinforce gender stereotypes about performance -i.e., females took on writing tasks, males took on technical "building" tasks. Gendered task orientation may be a possible explanation for results; this finding coheres with a study by Masi [25] who found that hands-on prototyping during team-based engineering design projects had a significant impact on the selfefficacy of first-year male engineering but not female engineering students. However, other explanations for why students engage (or not) in different tasks on team-based design projects may exist [30], [33], [34].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Chachra et al [38] found that tinkering and technical selfefficacy did not appear to change over the duration of a team-based engineering course, which they attributed to students taking on tasks that played to pre-existing strengths, which in some cases, reinforce gender stereotypes about performance -i.e., females took on writing tasks, males took on technical "building" tasks. Gendered task orientation may be a possible explanation for results; this finding coheres with a study by Masi [25] who found that hands-on prototyping during team-based engineering design projects had a significant impact on the selfefficacy of first-year male engineering but not female engineering students. However, other explanations for why students engage (or not) in different tasks on team-based design projects may exist [30], [33], [34].…”
Section: Discussionsupporting
confidence: 87%
“…Although logical, not all prior research supports the idea that more time spent by students on building prototypes has a direct positive correlation with engineering self-efficacy [31], [32]; in fact, Hirshfield and Chachra [33] found that fourth-year students do not have significantly high self-efficacy than first-year students. In other studies, first year engineering students' GPA [31] and individual course grades [25] were more predictive of self-efficacy than time spent prototyping or engaged in design tasks. Overall, previous research indicates student self-efficacy in engineering is malleable and multifarious psychological construct, influenced by multiple factors including course context, student demographics, types of learning opportunities, experiences with failure, relevant prior knowledge, and the emotions students experience during learning [32]- [34].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…By contrast, students with low self-efficacy may perceive that they can't learn the knowledge and skills necessary to be successful and/or will fail even if they work hard on a task. Research on self-efficacy [30,31,32] indicates that it plays an important role in academic motivation and persistence. Hirshfield and Chachra [34], for instance, suggested that student with low engineering self-efficacy may not take on more technical tasks in design projects.…”
Section: Introductionmentioning
confidence: 99%